2018
DOI: 10.1194/jlr.p087536
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of stratum corneum ceramides in Neu-Laxova syndrome caused by phosphoglycerate dehydrogenase deficiency

Abstract: Neu-Laxova syndrome (NLS) is a term that unifies the independent reports by Neu and Laxova of a lethal multiple congenital anomaly syndrome (1). The main features of NLS involve defective somatic growth and the disturbed development of the central nervous system and skin, as well as many other anomalies that might present primarily as malformations or a malformation sequence (1). In 2014, mutations in PHGDH, which encodes phosphoglycerate dehydrogenase (PHGDH), were found in autosomal recessive cases of NLS (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Three continuous SC tape strips (2.5 × 3.5 cm) were obtained from each lip site by making them evenly adhere with a finger for several seconds and then stripping an adhesive acrylic film (465#40; Teraoka Seisakusho, Tokyo, Japan). The samples were subjected to LC/MS analysis to assess the levels of 11 major ceramide species [5,15]. The tape strips were cut into two equal half‐strips: one half was used for ceramide measurement and the other half was used for quantifying protein.…”
Section: Methodsmentioning
confidence: 99%
“…Three continuous SC tape strips (2.5 × 3.5 cm) were obtained from each lip site by making them evenly adhere with a finger for several seconds and then stripping an adhesive acrylic film (465#40; Teraoka Seisakusho, Tokyo, Japan). The samples were subjected to LC/MS analysis to assess the levels of 11 major ceramide species [5,15]. The tape strips were cut into two equal half‐strips: one half was used for ceramide measurement and the other half was used for quantifying protein.…”
Section: Methodsmentioning
confidence: 99%
“…Neu–Laxova syndrome (NLS) is a lethal syndrome of intrauterine growth retardation and multiple malformations. The condition is most likely caused by mutations in the PHGDH, PSAT1, or PSPH genes, which are associated with the serine synthesis pathway [ 10 , 11 ]. Neu–Laxova syndrome type 1 is a more severe phenotypic variant of 3-PGDH deficiency.…”
Section: Congenital Microcephalymentioning
confidence: 99%
“…The mutation in the PHGDH gene (locus 1p12) occurs. Most PHGDH mutations that cause NLS are missense mutations, although nonsense, splicing or frame shift mutations have also been reported [ 11 ]. Acuna-Hidalgo et al, (2014) reported close parental consanguinity in few investigated families [ 10 ].…”
Section: Congenital Microcephalymentioning
confidence: 99%
“…Mutations in PHGDH , PSAT1 , and PSPH cause Neu–Laxova syndrome (NLS), which produces severe congenital anomalies in the central nervous system and diffuse erythematous skin lesions with scaling over the entire body [24]. An NLS patient with PHGDH deficiency demonstrated a significant reduction in 11 major classes of ceramides, including CerEOS, in the stratum corneum [24]. Thus, l ‐serine shortage caused by reduced activity of PHGDH is considered to lead to the ceramide reduction seen in the epidermis of NLS patients.…”
Section: Processes Of Acylceramide Synthesis and Cle Formation And Rmentioning
confidence: 99%
“…The other route of ceramide synthesis is a pathway using long‐chain bases which are produced de novo [23]. l ‐serine, a nonessential amino acid, is necessary for the de novo synthesis of long‐chain bases [24]. l ‐serine is made de novo from 3‐phosphoglycerate, a glycolytic intermediate, via three sequential reactions catalyzed in turn by phosphoglycerate dehydrogenase (PHGDH), phosphoserine aminotransferase 1 (PSAT1), and phosphoserine phosphatase (PSPH) [25].…”
Section: Processes Of Acylceramide Synthesis and Cle Formation And Related Ichthyoses Pathogenesesmentioning
confidence: 99%